Partisipasi Stakeholders dalam Penerapan Manajemen Berbasis Madrasah (MBM) Responsif Gender di MAN Insan Cendekia Gorontalo - Petta Solong, Najamuddin; Alhabsyi, Ni'ma M. (LP2M IAIN Sultan Amai Gorontalo, 2020)
This paper analyzes stakeholder participation in gender responsive Madrasah Based Management (MBM) with various supporting and inhibiting factors in MAN Insan Cendekia Gorontalo. The participation of stakeholders in gender responsive MBM is manifested in planning, implementing and evaluating activities that involve teachers, parents, communities, scientists, to contribute, abilities, roles, and aspirations to the achievement of educational programs related to community service for students, native speakers, and Economic Subject Teacher Deliberation (MGMP) activities independently by not differentiating between men and women in MAN IC Gorontalo. As for the supporting factors, first, the state will bear the financing through DIPA. Second, the density of student activities with the boarding school system. The first inhibiting factor is the dependence of funds on the government so that it does not provide room for participation. Second, the management of education personnel in a centralized manner.